SOCIAL-PSYCHOLOGICAL VARIABLES OF KINDERGARTEN AND GRADE ONE TEACHERS' CLASSROOM SUCH AS ANXIETY AND MOTIVATION TOWARD ENGLISH AS A MEDIUM OF INSTRUCTION IN REGARD WITH THEIR GENDER DIFFERENCES AND WORKPLACES - Khalid I. Mustafa; Alan S. Saadi I. (Universitas Islam Negeri Ar-Raniry, 2019)
The study aimed to find out the level of anxiety and motivation among kindergarten and grade one teachers toward teaching English as a medium of instruction, and also to figure out the correlation between anxiety and motivation, according to the selected variables. 42 grade one and kindergarten teachers randomly participated (10 males, 32 females). This study exercises Hopkins symptom checklist-25 for measuring anxiety and English Teacher Motivation Scale 30-items for measuring motivation that has been used. The result indicated that there is low level of anxiety and high level of motivation among participants. Moreover, there was a negative Pearson correlation between teachers' motivation and anxiety. The Level of anxiety was higher in female teachers. On the other hand level of motivation was higher in male teachers. Each demographic variable such as gender and workplace had effect on both teachers' motivation and anxiety.